2011
DOI: 10.3892/or.2011.1171
|View full text |Cite
|
Sign up to set email alerts
|

NAIF1 is down-regulated in gastric cancer and promotes apoptosis through the caspase-9 pathway in human MKN45 cells

Abstract: Abstract. Many key proteins are down-regulated or lose their function during cancer genesis and accelerate the progress of cancer. We found that nuclear apoptosis-inducing factor 1 (nAIF1) was highly expressed in normal gastric tissues but was down-regulated or lost in gastric cancer tissues (p<0.001). nAIF1 expression was higher in well-differentiated (p=0.004) than in moderately-or poorly-differentiated gastric cancer. nAIF1 expression was associated with different t stages (p=0.024). In vitro, nAIF1 can inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…The data presented herein is analogous to Luo's finding in tissues [10]. Moreover, we confirmed that NAIF1 is a nuclear protein in the gastric cancer cell lines MKN45 and BGC823.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The data presented herein is analogous to Luo's finding in tissues [10]. Moreover, we confirmed that NAIF1 is a nuclear protein in the gastric cancer cell lines MKN45 and BGC823.…”
Section: Discussionsupporting
confidence: 91%
“…The expression plasmids pEGFP-N1-NAIF1, which expresses a NAIF1-GFP fusion protein, and pEGFP-N1, which expresses green fluorescent protein (GFP), was kindly provided by Dr. Qing Luo [10].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In gastric cancer, NAIF1 inhibits gastric cancer migration and invasion by targeting MAPK or caspase-3. 13 , 14 In non-small-cell lung cancer, NAIF1 interacts with miR-24 to inhibit cancer growth. 15 In human prostate cancer, NAIF1 was suggested to be a potential biomarker, 16 yet its exact expression pattern or functional role remains elusive.…”
Section: Introductionmentioning
confidence: 99%